Burden of arrythmias in transgender patients hospitalized for gender‐affirming surgeries. Issue 4 (19th May 2020) - Antwi‐Amoabeng, Daniel; Doshi, Rajkumar; Adalja, Devina; Kumar, Ashish; Desai, Rupak; Islam, Raheel; Gullapalli, Nageshwara
Abstract: Background: We sought to describe the burden of arrhythmias and their impact on in‐hospital outcomes in transgender patients who underwent gender re‐assignment surgery. Methods: The study utilized data from the National Inpatient Sample from January 2012 to September 2015. Results: 16 555 adult transgender patients were included in this study. A total of 610 adults developed arrhythmia out of which atrial fibrillation (N = 475, 2.87%) was the most frequent arrhythmia. In‐hospital mortality increased substantially with arrhythmias. Conclusions: New‐onset arrythmias, while infrequent in the inpatient setting is associated with significantly higher in‐hospital mortality and resource utilization. Abstract : New‐onset arrhythmias were not frequent in patients undergoing gender‐affirming surgeries in the inpatient setting. Atrial fibrillation was the most common arrhythmia noted in this population. These arrhythmias, when developed, increases the risk of in‐hospital mortality and resource utilizations.